ANALISIS PENERAPAN PROGRAM REWARD KEPADA CUSTOMER MENGGUNAKAN METODE CLUSTERING - Novitasari, Dwi Tiyas; Barata, Mula Agung; Rochmatin, Novia Nur; Muzakka, Moch. Arifuddin; Andiyani, Putri (STIE-PMCI, 2024)
This research aims to analyze consumers to provide reward programs based on their satisfaction and loyalty in shopping centers [Malls]. The research was carried out by collecting data, then analyzing the results using relevant clustering methods. Regression analysis shows a strong relationship between these variables, and this research provides strong evidence for shopping centers and similar companies, to use this method to increase their customer satisfaction. These results can help companies design reward strategies that are more effective and in line with consumer preferences. This research contributes to the literature on customer management and marketing strategy by investigating their role in increasing satisfaction and loyalty. The practical implications of this research can help companies to maximize the benefits of their investment in rewards programs, by ensuring that the programs are not only attractive to customers but also effective in creating long-term loyalty.